Elemental characterization of Airbone Particulate Matter (APM) in Parit Buntar and Nibong Tebal - Abdul Haqi, Ibrahim; Nor Azam, Ramli; Mohd Talib, Latif (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my